Kualitas Dan Daya Simpan Kerang Hijau (Perna Viridis) Menggunakan Variasi Jenis Pengawet Alami Dan Lama Perendaman - HIKMAWATI, FARIDA; , Dra. Titik Suryani, M.Sc (2015)
Green shell (Perna viridis) is one of marine resources commodity with economic value and includes fovourite dish. in 100 grams of green shell meat contain 100 calories which are helpful for human body immune. Storability of green shelljust survive until 12 hours, shell slimy and fishy odor arestingingbecause it aleady damaged and spoiled. Natural preservative such as grapefruit leaf, kecombrang leaf, and pandan leaf have content that can inhibit microbial activitylike flavonoids, tannins, saponins, alkaloids, triterpenoids and its function as antimicrobial agent can be used to preserve green shell. The purposes for this research areknowing population of bacteria,quality of green shell with variation type of natural preservation and soaking time. Study design use randomized complete design using two factors. Factor 1 natural preservatives: grapefruit leaf extract (J1), kecombrang leaf extract (J2), pandan leaf extract (J3) and a factor 2: 13 hours soaking time (L1) and 17 hours (L2). Research shown that green shell has best quality in J2L1 treatment (kecombrang leaf extract with 13 hours of soaking time) with amount of bacetria population 2,1x107 Bacteria CFU / g, pH 6.3, 73.8% moisture content, and can survive for 3 days. Sensory test results shown that the green shell soaked in extract leaves (grapefruit, kecombrang, and pandan) for 13 hours and 17 hours Still can beconsumed